Policy challenges and approaches for the conservation of mangrove forests in Southeast Asia - Friess, D.A.; Thompson, B.S.; Brown, B.; Aldrie Amir, A.; Cameron, C.; Koldewey, H.J.; Sasmito, S.D.; Sidik, F. (Wiley, 2016)
Many drivers of mangrove forest loss operate over large scales and are most effectively addressed by policy interventions. However, conflicting or unclear policy objectives exist at multiple tiers of government, resulting in contradictory management decisions. To address this, we considered four approaches that are being used increasingly or could be deployed in Southeast Asia to ensure sustainable livelihoods and biodiversity conservation. First, a stronger incorporation of mangroves into marine protected areas (that currently focus largely on reefs and fisheries) could resolve some policy conflicts and ensure that mangroves do not fall through a policy gap. Second, examples of community and government comanagement exist, but achieving comanagement at scale will be important in reconciling stakeholders and addressing conflicting policy objectives. Third, private‐sector initiatives could protect mangroves through existing and novel mechanisms in degraded areas and areas under future threat. Finally, payments for ecosystem services (PES) hold great promise for mangrove conservation, with carbon PES schemes (known as blue carbon) attracting attention. Although barriers remain to the implementation of PES, the potential to implement them at multiple scales exists. Closing the gap between mangrove conservation policies and action is crucial to the improved protection and management of this imperiled coastal ecosystem and to the livelihoods that depend on them.